Post emergent herbicides in common bean crop and residual effect on maize crop - Torres, Diego Rafael Quispe (2018)
The present dissertation was divided into three chapters. In the first chapter, a literature review was carried out on bean culture in Brazil, followed by the chemical control of weeds in bean culture. Immediately afterwards the effects of the herbicides on the crop were added in succession. In the second chapter, the objective was to evaluate the post-emergence herbicides in weed control in different bean varietal groups. For this, six treatments were used alone or in a mixture, at different sowing times, to obtain information regarding efficiency in weed control, phytotoxicity and yield in bean cultivars. The results indicated that the herbicides were selective to bean cultivars. However, fomesafen alone and in combination with bentazon + imazamox had control efficiency. In the third chapter, the residual effect of the herbicides applied in the bean crop on the maize crop was objectified. A corn cultivar was selected as a crop in succession to the bean cultivars. The sowing was on the same experimental plots with the treatments of the herbicides in the different times of sowing to evaluate the phytotoxicity and the corn yield. It was verified that the isolated and mixed applications of the herbicides did not present negative effects in the corn crop. The evaluations also allowed to infer that the applications of the herbicides applied in the third bean harvest do not affect summer corn.